The role of interest in the transmission of social values - Clément, Fabrice; Dukes, Daniel (Frontiers in Psychology, 2013)
The environment is so rich with information that our cognitive system would be overloaded without a way to evaluate what is relevant for our needs and goals. Appraisal theory has shown how emotions, by ‘tagging’ the environment with differential values, enable the attribution of our attentional resources to what is most relevant in any given circumstances. Most often, however, the different cues triggering the allocation of attention are thought of as purely individualistic, like physiological needs or past encounters with certain stimuli. This approach is perfectly appropriate for objects, organisms or events that, by their intrinsic properties, are susceptible to affect the organism’s well being. But for humans, many aspects of the environment are culturally or temporally dependent: a soccer game may be highly relevant to some, but not at all to others. This paper contributes to a better understanding of the processes by which different elements of our social environment acquire values through our socialization process. We recruit different concepts proposed by developmental psychologists to shed some light on this social acquisition of relevance. The notion of joint attention, for example, is particularly important to understand how we are sensitive to the other’s focus of attention. Similarly, the term social referencing has been used to describe the process of taking into account the affective reaction to a given stimuli, in order to direct our behavior. At the core of this process, called “social appraisal” by Manstead, we propose that a specific emotion plays a major role: interest. Someone else’s expression of interest, which seems to be detectable from a very early age, is extremely useful in gauging what is worthy of attention among stimuli that are not inherently interesting. The paper highlights how external sources of information (the life experiences of community members) indicate what is relevant, thus giving access to the social values of that group.